Pengukuran Kinerja Keuangan Pemerintah Desa dengan Menggunakan Analisis Value For Money - Novi Khoiriawati; Isnah Mar’atus Sholikhah (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to measure the financial performance of Pucangsimo Village based on the concept of measuring public sector performance Value For Money. The researcher uses a descriptive quantitative approach with the type of case study research to measure and analyze the measurement results in the Pucangsimo Village APBDes Realization Report 2017, 2018, 2019, 2020, and 2021 which are viewed from the economic, efficiency, and effectiveness aspects. The data used are secondary in the form of the APBDes Realization Report for 2017 to 2021 fiscal year and primary data in the form of observations and interviews. The data analysis technique uses the Miles and Huberman model, namely 1) Data Reduction, 2) Data Presentation, and 3) Conclusion Drawing. The results showed that the financial performance of Pucangsimo Village from 2017 to 2021 was in the economic category. In terms of efficiency, 2018 and 2019 showed efficient results while 2017, 2020, and 2021 showed inefficient results. In terms of effectiveness, 2017, 2018, and 2019 showed effective results, while 2020 and 2021 showed quite effective results. This study provides information related to the existence of inefficiencies in controlling spending so that it can be a consideration for Pucangsimo Village to suppress spending activities while increasing the village original income by exploring and developing village potential. Keywords: Financial Performance, Village Government, Value For Money